2016
DOI: 10.1111/acem.12966
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Provides Noninferior Research Informed Consent for Remote Study Enrollment: A Randomized Controlled Trial

Abstract: Objective Telemedicine networks are beginning to provide an avenue for conducting emergency medicine research, but using telemedicine to recruit participants for clinical trials has not been validated. The goal of this consent study is to determine whether patient comprehension of telemedicine-enabled research informed consent is non-inferior to standard face-to-face research informed consent. Methods A prospective, open-label randomized controlled trial was performed in a 60,000-visit Midwestern academic Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…The quality of the included studies varied widely. Among the randomized controlled trials, only 3 studies [ 25 - 27 ] received a quality score of 3. Quality scores of 2 and 1 were provided to 1 study [ 28 ] and 6 studies [ 29 - 34 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the included studies varied widely. Among the randomized controlled trials, only 3 studies [ 25 - 27 ] received a quality score of 3. Quality scores of 2 and 1 were provided to 1 study [ 28 ] and 6 studies [ 29 - 34 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies [ 28 , 33 , 34 , 39 , 44 - 46 , 48 , 55 , 60 , 62 ], the majority of participants had a high level of education. It should also be noted that a number of studies [ 27 , 29 , 51 ] assessing comprehension did not report the education level of their participants. Therefore, there might be additional barriers for less educated participants to achieving an adequate level of understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Such capabilities can take the form of telemedicine, where researchers connect remotely but in real time with prospective participants, or manifest in online or mail-based strategies. One recent randomized trial has shown that telemedicine is not inferior to a face-to-face informed consent process, in terms of patient-reported understanding [ 10 ]. And in a recent worldwide online survey ( N = 12,427), 60% of respondents reported the use of some form of technology in their clinical studies, most commonly taking the form of text messaging (18%), use of a tablet for informed consent (17%), use of a smartphone app (10%), and use of wearable devices (8%) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, researchers found noninferior informed consent using telemedicine for remote study enrollment; understanding of consent and accrual rates of participation were similar between face-to-face and telemedicine groups. 11 …”
Section: Discussionmentioning
confidence: 99%